Structural evolution of cell types by step-wise assembly of cellular modules - Achim, Kaia; Arendt, Detlev (Current opinion in genetics & development, 2014)
Cell types are composed of cellular modules exerting specific subfunctions. The evolutionary emergence and diversification of these modules can be tracked through the comparative analysis of genomes. Here, we survey recent advances elucidating the origin of neurons, of smooth and striated muscle cells and of the T- and B-cells of the immune system in the diverging lineages of animal evolution. Gene presence and absence analyses in various metazoan genomes allow mapping the step-wise assembly of key modules - such as the postsynaptic density characteristic for neurons or the z-disk characteristic for striated muscle - on the animal evolutionary tree. Using this approach, first insight into the structural evolution of cell types can be gained.